2017
DOI: 10.3390/ma10010045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Composition and Active Property Evaluation of Certain Essential Oils to Assess their Potential Applications in Active Food Packaging

Abstract: The antifungal, antibacterial, and antioxidant activity of four commercial essential oils (EOs) (thyme, clove, rosemary, and tea tree) from Romanian production were studied in order to assess them as bioactive compounds for active food packaging applications. The chemical composition of the oils was determined with the Folin–Ciocâlteu method and gas chromatography coupled with mass spectrometry and flame ionization detectors, and it was found that they respect the AFNOR/ISO standard limits. The EOs were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…The phenolic compounds in clove leaf oil are similar to those in clove bud oil, and the concentration of eugenol in clove bud oil and clove leaf oil is in the range of 72.08–82.36% . Compared with other essential oils, it was reported that clove oil showed higher phenolic content and radical‐scavenging activities …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic compounds in clove leaf oil are similar to those in clove bud oil, and the concentration of eugenol in clove bud oil and clove leaf oil is in the range of 72.08–82.36% . Compared with other essential oils, it was reported that clove oil showed higher phenolic content and radical‐scavenging activities …”
Section: Resultsmentioning
confidence: 99%
“…Clove ( Syzygium aromaticum ) leaf oil consists of eugenol as the main component, followed by β‐caryophyllene and α ‐humulene, which exhibit high oxygen‐scavenging activity . Despite their similar chemical compositions, clove bud oil has been investigated more than clove leaf oil for use in food preservation . The phenolic compounds in clove leaf oil are responsible for both the antimicrobial and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%
“…-dispersion/dissolution of the polymer and all active components in a common solvent that is subsequently evaporated (solution casting technique)-method that can also be used as a coating technique by casting the dissolution onto the particular surface [43]. [48].…”
Section: Polyphenols Plant Extracts Essential Oilsmentioning
confidence: 99%
“…Rosemary EOs exhibit antifungal activity against Fusarium graminearum (cereal pathogen), α-pinene and 1,8-cineole contained in the oil show activity against, C. albicans, and A. niger [81]. Rosemary oil also exhibits bacteriodical and bacteriostatic activity against S. aureus, Bacillus subtilis and P. aeruginosa [83].…”
Section: Rosemary (R Officinalis)mentioning
confidence: 99%